Pengaruh Human Relation dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan pada Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Utara - Wanda Febrianti; Alfi Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study examines the influence if human relations and human resource development on employee performance et the National Amil Zakat Agency (BAZNAS) if North Sumatra Province. The population if this study consists of all employees of BAZNAS in North Sumatra Province, totaling 23 individuals. The research employs a saturated sampling method (census), where all population members are included as samples. Data collection is conducted through observation and questionnaires, utilizing the Slovin formula to determine sample size with a 1% error rate. Both primary and secondary data are collected, and data analysis is performed using a qualitative associative method. Various tests are conducted, including validity testing, reliability testing, classic assumption testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, t-tests, F-tests, and R2 tests, utilizing SPSS software. The results if they first hypothesis testing indicate that they human relations variable has a positive and significant influence on employee performance at BAZNAS in North Sumatra Province. However, the results of the second hypothesis testing reveal that the human resource development variable also has an positives and significant influence on employee performance at BAZNAS in North Sumatra Province. Thus, based on these research findings, it can be concluded that human resource development has a stronger influence on employee performance compared to human relations at BAZNAS in North Sumatra Province.